IPv6 transition using dual stack mechanism / Noriah Ibrahim - Ibrahim, Noriah (2014)
In a matter of very few years, the Internet consolidated itself as a very powerful platform that has changed forever the way we do business, the way we communicate and the way we live. The Internet is a global system of interconnected computer networks that use the standard Internet Protocol Suite (TCP/IP) to serve several billion users worldwide. Therefore, this project will use the new technologies for enhance the best product of doorbell. The Doorbell Automation System is one of the products that adopt advanced technology. It focused in used a new platform such as Raspberry Pi as a CPU that will integrate the device attached near the door. The objectives of this project is to give a function of device attach such as camera and button. All the devices will integrate each other and the raspberry pi function as a main control unit where it will connect to the database. The functions of raspberry pi as a platform that will send the image information to be saved in database. This project has the capability to send and retrieve an image thru mobile. As a result of this project, the devices system are develop with programming code and the data are save successfully in the database thru Internet. This product will satisfy the different requirement of various residential house and high-storied buildings. With connection to the network, this doorbell will integrate to the system that sends an image to be record in the system. It will be good assistant if residential house need security for apartment building or home and the file image can be view in anytime at anywhere.